2014
DOI: 10.1186/preaccept-1557435139144520
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain and N-acetylcysteine inhibit proliferation and survival of gastrointestinal cancer cells in vitro : significance of combination therapy

Abstract: BackgroundBromelain and N-acetylcysteine are two natural, sulfhydryl-containing compounds with good safety profiles which have been investigated for their benefits and application in health and disease for more than fifty years. As such, the potential values of these agents in cancer therapy have been variably reported in the literature. In the present study, the efficacy of bromelain and N-acetylcysteine in single agent and combination treatment of human gastrointestinal carcinoma cells was evaluated in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 55 publications
4
23
0
Order By: Relevance
“…Recent studies suggest that antioxidants accelerate tumor migration and metastasis . In direct contrast, other work has found that antioxidant administration prevents cancer proliferation, invasion, migration and metastasis …”
Section: Cancer Metabolism Is Contextual: a Ros‐dependent Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies suggest that antioxidants accelerate tumor migration and metastasis . In direct contrast, other work has found that antioxidant administration prevents cancer proliferation, invasion, migration and metastasis …”
Section: Cancer Metabolism Is Contextual: a Ros‐dependent Modelmentioning
confidence: 94%
“…64,[82][83][84] In direct contrast, other work has found that antioxidant administration prevents cancer proliferation, invasion, migration and metastasis. 36,37,[85][86][87][88][89][90] The differing effects of ROS modulation are context dependent. Cells with low oxidation status may seek to enhance their ROS signaling for a survival and motility advantage.…”
Section: Cancer Metabolism Is Contextual: a Ros-dependent Modelmentioning
confidence: 99%
“…In addition to the above clinical applications, NAC has been employed as a potent anti-oxidant in several experimental models of infection and cancer in vitro and in vivo [1520]. In these settings, NAC serves as a pro-drug to L-cysteine, which is a precursor to the biologic antioxidant glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…These include P-388 leukemia, sarcoma (S-37), A-431 epidermoid carcinoma, A-375 melanoma, lewis lung cancer and ADC-755 breast cancer (Bhui et al 2011;Pavan et al 2012). Furthermore, the use of bromelain in conjugation with chemotherapeutic medicine improves the efficiency of these drugs to certain extent (Pillai et al 2013;Amini et al 2014). …”
Section: Anti-cancer Agentmentioning
confidence: 99%